HUBUNGAN ADIKSI ONLINE GAME DENGAN MOTIVASI BELAJAR PADA SISWA SEKOLAH MENENGAH PERTAMA DI JAKARTA UTARA - Gladys Jane Octavia; Surilena Surilena; Erfen Gustiawan (Bahasa Indonesia, 2020)
Introduction: Online game addiction is a disorder with uncontrolable behavioral when playing online games. The academic achievement may decrease and has been negatively affected due to lack of learning motivation. The purpose of this study was to explore the relation between online game addiction and learning motivation among junior high school students in north Jakarta.Methods: A cross-sectional study was conducted in 1,474 junior high school students by filling in the questionnaire, consisting of the Indonesian Online Game Addiction Questionnaire (IOGAQ) and the Motivation Learning Strategy Questionnaire (MSLQ). The inclusion criteria were all junior high school (SMP) class I to class III in Kelurahan Penjaringan, North Jakarta. The exclusion criteria were students who did not signed the consent form. Bivariate test and multivariate logistic regression test were performed to analyze data.Results: From 1,474 respondents, most of them (52.5%) were aged 14 years old and girls (37.8%). The addiction to online game was more prevalent in boys (90.1%) and girls (79.1%), mostly (87.3%) in grade 1 junior high school. The respondents with online game addiction often played online games ≥4 days/week (95%), with the duration of playing online games on school days (95.5%) or holidays (94.2%) was >4hours/day. The types of online games played was role playing games (85.8%) using a portable tool (94,8%). The learning motivation was low (86.3%). Interestingly, bivariate analysis showed no significant relationship between online game addiction and learning motivation (p≥0.05).Conclusion: There is no significant relation between online game addiction and learning motivation. However, online game addiction need to be closely monitored as this may impact the learning motivation.